Effects of TI and Sr-site substitutions on TlSr2CaCu2O7 superconductors / Ahmad Kamal Hayati Yahya, Norazila Ibrahim and Faizah Md. Salleh - Yahya, Ahmad Kamal Hayati; Ibrahim, Norazila; Md. Salleh, Faizah (2001)
The discovery of superconductivity at temperatures above 77 K is amongst one of the important scientific events of the past decade. The potential scientific and commercial importance of this discovery, largely underlie the degree of excitement and fervour of the field. Superconductors are elements, inter-metallic alloys, or compounds that will conduct electricity without resistance below a certain temperature. Superconductivity has been found in at least 26 metallic elements and in thousands of alloys and compounds.